WORK-FROM-HOME PRODUCTIVITY IN INDONESIA: FIRST TIME EXPERIENCE OF VIRTUAL WORKING DURING COVID-19 TIME - Nopriadi Saputra; Hayat Hayat; Farid Ardyansyah; Dyah Palupiningtyas; Khanifatul Khusna; Okta Karneli (LIPI Press, 2021)
During COVID-19, working from home (WFH) becomes most possible working arrangement alternative in order to practice social distancing. The productivity of WFH is still questioned by many organizations, especially companies which conduct WFH extensively for the first time. Do digital skills, work motivation, digital leadership, digital collaboration, perceived organizational support, and performance management impact positively and significantly on work productivity? This paper is based on cross-sectional study which involved 855 office workers from 32 provinces in Indonesia. PLS SEM and SmartPLS version 3.0 were used to structure and test the research model. The analysis result reveals that individual factor influences WFH productivity directly, while group and organizational antecedents influenced indirectly. To leverage WFH productivity, organizations should focus to develop digital skills and work motivation as individual factor. The organizational and group antecedents should be aligned and directed to impact on WFH productivity.